Supraventricular Tachycardia in Pregnancy - Prabhu Gauri1 , Shubha SR2 , M.B.Bellad3 , Metgud Shridevi2 (Perspectives In Medical Research, 2020)
INTRODUCTION: The commonest arrhythmia in women of reproductive age, is paroxysmal supraventricular tachycardia (SVT). We present a rare case of SVT who presented for the first time during pregnancy, who failed to respond to Electrical cardioversion(ECV), but reverted back to sinus rhythm by secondline pharmacotherapy. PROCEDURE: A 22 year old primigravidapresented at 37weeks in labour with complaints of breathlessness and severe palpitations when she was diagnosed to have supraventricular tachycardia(SVT) on ECG and was referred to a tertiary care centre for further management.Pharmacological cardioversion was attempted with intravenous diltiazem, but in vain. Decision was taken for electrical cardioversion with synchronized DC shocks of 50 joules and 100 joules successively, but was not successful too. As a last resort, bolus of intravenous Amiodarone 150 mg was given over 10 minutes followed by infusion at the rate of 24 mg per hour(2ml/hr), which finally brought down the heart rate to 98bpm. In view of non-reassuring fetal heart rate observed on CTG, patient was taken up for an emergency caesarean section under epidural anaesthesia with grave risk consent and shifted to ICCU post-operatively. RESULT: Patient delivered a male baby of birth weight 2.35kg. Patient tolerated the surgery well and did not experience any episodes of PSVT throughout the intra-operative period. Postoperatively patient was managed in consultation with cardiologist. Amiodarone infusion was continued for 24 hours at 24mg/ hour. Post-operative period was uneventful, patient was started on oral anti arrhythmic medications and discharged on the same. CONCLUSION : Accurate diagnosis, regular follow up and multidisciplinary approach during acute episode and during delivery can prevent life threatening risks that might be posed to the mother and fetus in a case of PSVT. Treatment options include nonpharmacological therapy, followed by adenosine and other drugs if required, and lastly electrical cardioversion